Developing country consumers’ acceptance of biofortified foods: a synthesis - Birol, Ekin; Meenakshi, J.V.; Oparinde, Adewale; Pérez, Salomón; Tomlins, Keith I. (Springer, 2015)
The success of biofortified staple crops depends on whether they are accepted and consumed by target populations. In the past 8 years, several studies were undertaken to understand consumers’ acceptance of foods made with biofortified staple crops. Consumer acceptance is measured in terms of their sensory evaluation and economic valuation of biofortified varieties vis-à-vis conventional ones. These studies apply expert sensory panel and hedonic trait analyses methods adopted from food sciences literature, as well as various preference elicitation methods (including experimental auctions, revealed choice experiments, and stated choice experiments) adopted from experimental economics literature. These studies also test the impact of various levers on consumers’ evaluation and valuation for biofortified foods. These levers include (i) nutrition information and the media through which such information is conveyed; (ii) the length and content of nutrition information; (iii) different branding options; (iv) the nature (national or international) of the branding/certification agency that is endorsing the biofortified staple food; and (v) the nature (national or international) of the agency that is delivering the biofortified staple food. This paper brings together evidence on consumer acceptance of biofortified crops on 5 crops across 7 countries in Africa, Asia and Latin America. The results of these studies are expected to aid in the development of biofortified crops that consumers like, as well as in the development of appropriate marketing and consumer awareness or information campaigns to encourage the switch in consumption from traditional staples to biofortified ones.